Ten Rules for the Management of Antiphospholipid Syndrome - Zhao, Jiuliang (Journal of clinical rheumatology and immunology (Online), 2024)
2023 ACR/EULAR APS classification criteria started a new era for doctors to comprehensively understand this disease. According to current research evidence and clinical practice experiences, we summarize 10 rules for management of APS as followed: Rule 1: APS is a systemic autoimmune disease with multi-systemic involvement and heterogeneity of clinical phenotypes. Rule 2: Each APS related thrombotic event requires a comprehensive assessment of “risk factors”. Rule 3: APS arterial n venous events w/ different mechanisms require separate predict models of recurrency. Rule 4: APS-related arterial thrombosis are not only “thromboembolic” but also “vasculopathic”. Rule 5: Microangiopathy is an unawareness and underestimated but pivotal phenotype of APS. Rule 6: Effective screening & timely diagnosis of APS-valvular heart diseases are crucial for prevention and prognosis improvement. Rule 7: APS-related hematological involvement includes thrombocytopenia & autoimmune hemolytic anemia. Rule 8: Significant heterogeneity of OAPS indicates different mechanisms and the necessity of stratification before Treatment. Rule 9: APLs is one of major contributing factors related irreversible organ damage in SLE Rule 10: Treatment of APS requires individualized precision stratification strategies including immunomodulators.